Voter Reaction to Government Incompetence and Corruption Related to the 1999 Earthquakes in Turkey - Ali T. Akarca; Aysit Tansel (Institute for the Study of Labor (IZA), 2015)
Two major earthquakes which struck northwestern Turkey in 1999 exposed rampant corruption involving construction and zoning code violations. The government's relief efforts were tainted by corruption as well, and exhibited a great deal of incompetence. How voters responded to these in the next election held in 2002 is investigated. The fact that different group of parties were responsible for the construction of the shoddy buildings, and for the corruption and mismanagement related to relief, provided us with a unique opportunity to determine whether and how the electorate punished the culprits for each of these. Vote equations are estimated for the seven major political parties. These are fitted to cross-provincial data individually, using OLS, Robust Regression methods, and Seemingly Unrelated Regressions procedures. The same picture emerges from each of these methods. Not just those ruling at the time of the earthquakes, but also other parties which were in power when the substandard buildings, were built were held accountable by the electorate. Furthermore, the Turkish voters appear to have allocated the blame rationally, taking into consideration the division of labor in the central government, and the relative influences the parties had on local administrations. Reaction of the voters to government incompetence and corruption was one of the factors which resulted in the emergence of a new party system. In 2002, the AKP, established only a year before, captured almost all of the far-right Islamist, about half of the far-right nationalist, and more than half of the center-right votes in 2002.
Keywords: D72; D73; H84; Q54; 330; natural disaster; corruption; disaster aid; governance; election; voter behavior; voter turnout; Turkey